2015
DOI: 10.5152/tpd.2015.3293
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Isolated Pancreatic Hydatid Cyst

Abstract: Isolated pancreatic hydatid cysts are a rare parasitic disease even in endemic areas. It is difficult to discriminate primary pancreatic hydatid cysts from other cystic and solid lesions of the pancreas. This is a case report of an incidental isolated pancreatic hydatid cyst. A heterogeneous cystic lesion in the body of the pancreas was identified on magnetic resonance imaging of a patient previously diagnosed patient with cholelithiasis, and because of the malignant possibility of the lesion, splenectomy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…It has also been reported that 9.3% of these lesions perforate in a spontaneous way or rupture into the peritoneal space (23). In the differential diagnosis, it is important that pancreatic pseudocysts and cystic malignancies of the pancreas are kept in mind (23). Both of our cases were primary HCs located in the distal pancreas.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…It has also been reported that 9.3% of these lesions perforate in a spontaneous way or rupture into the peritoneal space (23). In the differential diagnosis, it is important that pancreatic pseudocysts and cystic malignancies of the pancreas are kept in mind (23). Both of our cases were primary HCs located in the distal pancreas.…”
mentioning
confidence: 64%
“…Parasites may settle in almost every site of the body forming primary HC (10). Liver and lung are reported as the most frequent locations, yet unusual sites such as peritoneum, retroperitoneum, spleen, kidney, heart, pelvic, urinary tract, bladder, bone, soft tissue, pancreas, gallbladder, inguinal, supraclavicular, cerebral, spinal cord, and abdominal wall have also been described (4,6,7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). secondary HC mostly occurs after spontaneous or travmatic rupture of a cyst in abdominal cavity when free protoscolices and/or tiny cysts develop to become larger cysts (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreas being a rare location for this disease is not frequently affected even in endemic regions with less than 1% incidence [3]. Isolated pancreas involvement being rare demonstrates distinct features.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite ova are transported from the small bowel via the hematogenous route; in more than 50% of cases, it affects the liver; it is also able to spread into other organs like the lungs, spleen, brain, bones, retroperitoneal space, and muscles [1-2]. A hydatid cyst is rather rarely seen solely in the pancreas, as in other rare locations it mostly manifests in the pancreas as part of a multiple site involvement [2-3]. Isolated involvement of the pancreas is rare and is mostly seen in endemic regions accounting for nearly 0.2%-1% of the cases [2-4].…”
Section: Introductionmentioning
confidence: 99%